Banking efficiency between concept and measurement methods - الخزرجي, ثريا عبد الرحيم; بتال, احمد حسين (Journal of Economics and Administrative Sciences, 2012)
The research aims to review the concepts of banking efficiency and its relationship to performance, productivity and efficiency, as well as analyze the efficiency of the banking in micro-economic view. In order to achieve the objectives of the research We have been employed graphic, Econometrics  and Mathematical methods to derive the different concepts of banking efficiency.We showed that there are two main methods used to measure the bank efficiency, the first called Stochastic Frontier Analysis , this technique depends on the parametric methods, The other method is called Data Envelopment Analysis is based on mathematical programming methods